Novel approach towards the functionalization of ISAF carbon black for reinforcing acrylonitrile butadiene rubber. (2022) - Paul, Asha; David, Deepthi Anna; Balakrishnan, Neethu T.M.; Das, Akhila; Sameeha, A.P.; Fatima, M.J. Jabeen; Raghavan, Prasanth
Abstract: The dispersion and distribution of fillers are the critical factors that influences the properties of rubber composites and is strongly affected by the agglomeration of particles. Carbon black (CB), the principal filler in rubber industry, counters on its incomplete dispersion in rubber latex due to limited polar groups on its surface. Thus, sulphuric acid (H2 SO4 ) functionalization of CB with varying concentrations (20%, 40% and 60% v/v. %) in inert N2 atmosphere adopted for enhanced dispersion and increased compatibility of CB in acrylonitrile butadiene rubber (NBR) latex. In the present study, an inorganic acid is employed to treat ISAF CB to enhance the compatibility of the filler in NBR, thereby to improve the dispersion and mechanical properties of the rubber composites. Further, the acid functionalized CB and their composites were characterized. The acid modified CB dispersed NBR latex composites show superior cure characteristics, mechanical and dynamic mechanical properties compared to NBR-CB composite.